2001
DOI: 10.1055/s-2001-16569
|View full text |Cite
|
Sign up to set email alerts
|

Anastomosenprotektion durch transanale Drainage? - Klinische Erfahrung bei 50 Patienten nach Rektumresektionen mit totaler mesorektaler Exzision und tiefen Anastomosen -

Abstract: Between October 1998 and December 1999 50 patients with a primary cancer of the rectum were treated by sphincter saving anterior resection of the rectum and total mesorectal excision. Eight patients were given a neoadjuvant combined radio-chemotherapy. The anastomoses were performed in the triple-stapling technique with a Premium Plus CEEA stapling device (Fa. Tyco Health Care, Tönisvorst, Germany) or with a Proximate ILS curved stapling device (Fa. Ethicon Endo Surgery, Norderstedt, Germany). The anastomoses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…In Germany, Sterk et al [ 24 ] used a 40-cm long transanal rubber drain in 50 patients. 10% of the patients developed an anastomotic leakage, 4% with a clinically evident anastomotic leakage and 6% with an asymptomatic anastomotic leakage detected by CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Germany, Sterk et al [ 24 ] used a 40-cm long transanal rubber drain in 50 patients. 10% of the patients developed an anastomotic leakage, 4% with a clinically evident anastomotic leakage and 6% with an asymptomatic anastomotic leakage detected by CT.…”
Section: Discussionmentioning
confidence: 99%
“…10% of the patients developed an anastomotic leakage, 4% with a clinically evident anastomotic leakage and 6% with an asymptomatic anastomotic leakage detected by CT. The authors consider the transanal drain as at least equivalent to a conventional colostomy in terms of reducing symptomatic anastomotic leakage [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty‐nine observational studies met the inclusion criteria [20–58]. These studies reported data on 4059 patients after TME for rectal cancer.…”
Section: Methodsmentioning
confidence: 99%
“…longer hospital stay, reversal procedure, greater inpatient costs, permanent stoma, stoma-related complications, and patient discomfort) [14,15]. Given the evidence that increased intraluminal rectal pressure is among the major contributors to AL [16][17][18][19], several endorectal devices (e.g. transanal tube cuff rectum, drainage tube, silicone transanal tube) have been proposed as promising alternatives to defunctioning stoma [13,[20][21].…”
Section: Introductionmentioning
confidence: 99%